Studi Eksperimen Penambahan Limbah Kaca Bening (Float Glass) dan Cangkang Kerang Hijau (Perna viridis) pada Efektivitas Cat Waterproofing - Nais Sofina Zulfa; Luthfiah Ajeng Herdiartanti; Riza Susanti; Hartono Hartono (Jurnal Sipil dan Arsitektur, 2025)
Walls are important elements in a building that function as a divider between rooms and as a protector from external factors. Common damage to walls is caused by water or damp conditions. Water that seeps into the wall can cause damage, reduce quality and durability. The use of waterproofing paint is a solution to overcome this problem. Waterproofing paint has been widely developed with various innovations. With the addition of additives to the paint, waterproofing can be increased. Therefore, paint additives are needed in the form of glass powder to keep the wall surface from being damp and green mussel shell powder which contains calcium carbonate (CaCO3). The purpose of this study was to determine the water resistance of paint added with clear glass powder with percentage variations of 10%, 15% and 20% and green mussel shell powder with a substitution of 5%, 7,5% and 10% with each test object 1 liter of paint. Based on the results of the water seepage test, it has not met SNI requirements. However, the water absorption, specific gravity, spreadability and drying time tests have met SNI requirements. Adhesion testing for all paint variations has met ASTM D3359 requirements.